(untitled) (Transport systems and technologies, 2018)
High speeds and increased load dictate higher requirements not only to the strength characteristics of running parts, but also to the support system of the car. In order to ensure the strength of bearing systems, appropriate regulatory documentation, spinal beams subjected to mechanical or thermal straightening. Thermal correction of local deformation consists in the fact that after the local heating in the metal sheet having plastic deformation «truncation» that clean «extra» metal. The effectiveness of the thermal changes depends on a large number of parameters, which is the main problem of implementation of this process step. One way to solve this problem − optimization of the heating parameters, number and location of heating spots based on mathematical modeling of the thermal changes for each of the deformed portion.